Public Library Summer Reading Programs Contribute to Reading Progress and Proficiency - Bogel, Gayle (Evidence Based Library and Information Practice, 2012)
Abstract Objectives – To explore summer reading partnerships between public libraries and school libraries, and the impact on student achievement in reading. Design – The design is mixed methods: tests, interviews and surveys. Setting – Eleven US sites involving school and public library partners. Subjects – A total of 357 elementary school students entering fourth grade that met specific criteria. Parents, teachers, school librarians and public librarians were also included. Methods – This study occurred over a three year period from 2006-2009. It was developed as a partnership between Dominican University, the Colorado State Library Agency and the Texas Library and Archives Commission. Additionally, the Center for Summer Learning at Johns Hopkins University was contracted to conduct the research. It was designed to explore the research question central to a 1978 study by Barbara Heyns. An advisory committee, with representatives from each partner agency, developed evaluation questions and established the objective selection criteria for participants in the study. The criteria included: at least 50% of students qualifying for free and reduced price meals; at least 85 percent of school population would take the reading proficiency test in English; public library summer reading programs with a minimum of six weeks of programming; a history of collaboration between the paired school and public library applicants; both school and public library would sign a partnership agreement and participate in conference calls. In spring of 2008, students at participating sites were given a pre-test using the Scholastic Reading Inventory, and also provided with special summer reading logs developed for the study, to be used during their subsequent participation in the public library summer reading programs. In fall of 2008, the same children were tested on the Scholastic Reading Inventory. In addition, surveys of students, parents, teachers and library staff were administered, as well as a structured interview of library staff. Main Results – The students who participated in the public library summer reading program did not experience summer loss in reading as measured by the post test administered in their schools. The researchers note patterns in the demographics of students who chose to participate (participation was self-selected and voluntary): predominantly Caucasian girls above poverty level, who generally scored well on reading tests. Those who participated in the study also used libraries, had more books in their homes, and parents who used libraries and provided literacy activities at home. Teachers found that students who participated in the program started the school year ready to learn, had improved reading achievement and displayed stronger motivation, enjoyment and confidence in reading. Parents of students who participated in the program also strongly agreed that their children where better prepared to begin the school year. Conclusion – The results from this study confirmed findings from an earlier study (Heyns, 1978) and subsequent related research that summer reading programs in public libraries can contribute to maintaining reading progress and proficiency, and that the recreational reading that is available to all students regardless of socioeconomic status through the public library can make a difference in reading scores. In this article the researchers presented results and conclusions based on selected subsets of the results in the full study. The participants were self-reported and no control group was established. The researchers also use the results of the study as a starting point to provide a call to action that highlights the value of public library summer reading programs, and the need for the education community to invest in partnerships with public libraries, particularly in communities that serve children and families in low-economic or depressed areas. They also note the need to include parents and grandparents in outreach efforts.